2013
DOI: 10.1016/j.ejvs.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Lower Prevalence than Expected when Screening 70-year-old Men for Abdominal Aortic Aneurysm

Abstract: When screening 70-year-old men for AAA, the prevalence was less than half that expected, despite a high attendance rate. Smoking was the strongest risk factor. Almost 40% of the men with AAAs were already known from other means than screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
3
29
1
Order By: Relevance
“…Four biggest RCTs reported the prevalence of AAA in male populations at the level from 4% to 7.2% [15][16][17][18], however, some recent studies suggested changing epidemiology of AAA. The screening prevalence rates of 1.1-1.7% have been recently reported [9,21]. Our study seems to confirm that trend.…”
Section: Discussionsupporting
confidence: 89%
“…Four biggest RCTs reported the prevalence of AAA in male populations at the level from 4% to 7.2% [15][16][17][18], however, some recent studies suggested changing epidemiology of AAA. The screening prevalence rates of 1.1-1.7% have been recently reported [9,21]. Our study seems to confirm that trend.…”
Section: Discussionsupporting
confidence: 89%
“…The estimate for AAA prevalence of 3·3 per cent, based on 2008–2011, appears to have decreased since the last Danish estimates from a randomized trial in 1994–1998 where it was 4·0 per cent. In a similar Swedish trial a prevalence of 3·4 per cent was recorded for 2008–2010. The prevalence is strongly associated with age.…”
Section: Discussionmentioning
confidence: 88%
“…Only 22⋅3 per cent of incident events occurred in men aged 65-74 years ( Table 1), and 13 per cent (8 of 61) of aneurysm-related deaths. Some 33 of the 35 events at age below 75 years occurred in current (24) or previous (9) smokers ( Table 1), with a higher prevalence of current smokers (P < 0⋅001) in patients with acute events than in the underlying study population ( Fig. 3 and Table S1, supporting information).…”
Section: Resultsmentioning
confidence: 96%